2018
DOI: 10.3389/fimmu.2018.00699
|View full text |Cite
|
Sign up to set email alerts
|

Clec9a-Mediated Ablation of Conventional Dendritic Cells Suggests a Lymphoid Path to Generating Dendritic Cells In Vivo

Abstract: Conventional dendritic cells (cDCs) are versatile activators of immune responses that develop as part of the myeloid lineage downstream of hematopoietic stem cells. We have recently shown that in mice precursors of cDCs, but not of other leukocytes, are marked by expression of DNGR-1/CLEC9A. To genetically deplete DNGR-1-expressing cDC precursors and their progeny, we crossed Clec9a-Cre mice to Rosa-lox-STOP-lox-diphtheria toxin (DTA) mice. These mice develop signs of age-dependent myeloproliferative disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 89 publications
1
21
1
Order By: Relevance
“…Notably, YFP labeling also suggests an age-dependent heterogeneity of CD11b hi cells. Because monocytes and lymphoid progenitors can contribute to macrophage and DC-like cells, 1,11,17,[69][70][71] these cells could also be putative progenitors of CD11b hi and F4/80 hi cells in early life, which needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, YFP labeling also suggests an age-dependent heterogeneity of CD11b hi cells. Because monocytes and lymphoid progenitors can contribute to macrophage and DC-like cells, 1,11,17,[69][70][71] these cells could also be putative progenitors of CD11b hi and F4/80 hi cells in early life, which needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies across both humans and mice have increasingly shown that cDCs and putative Axl + DCs can also be derived from both myeloid and lymphoid progenitors (8991). This collectively reflects a paradigm shift in our understanding of haematopoiesis, moving away from a model of homogenous multipotent progenitors that bifurcate into distinct but rigid cell fates (i.e., MDP bifurcation into macrophage or dendritic cell fate) and instead toward one where lineage is imprinted early during development in early progenitors, possibly prior to the emergence of distinctive phenotypes (9299).…”
Section: Dendritic Cell Subsets and Ontogenymentioning
confidence: 99%
“…This is also the case for the pre-cDCs, which already contain pre-cDC1, and pre-cDC2 (13, 14). In contrast, pDCs are also produced from a lymphoid progenitor (LP) (15) in the steady state whereas this happens for cDCs only in situation of cDC ablation (16).…”
Section: Introductionmentioning
confidence: 99%